AB0521 COST OF ILLNESS OF ANCA-ASSOCIATED VASCULITIS IN ITALY: DATA LINKAGE ANALYSIS OF MULTIPLE CLINICAL AND ADMINISTRATIVE DATABASES IN THE PROVINCE OF UDINE, ITALY. (2nd June 2020) - Quartuccio, L.; Treppo, E.; De Vita, S.; Valent, F.
Abstract : Background: ANCA-associated vasculitides (AAV) are a group of systemic vasculitis carrying a high risk of hospitalization because the multiorgan involvement, the acute nature of some clinical manifestations, the chronic but very disabling course of some other manifestations and finally the risk of severe infections due to chronic glucocorticoid and immunosuppressor administration. However, data on cost of illness due to AAV are lacking. Objectives: to estimate the cost of illness in patients suffering from AAV in the province of Udine (about 500, 000 inhabitants), Friuli Venezia Giulia (FVG), Italy, from year 2010 to 2018. Methods: integration of the information coming from many administrative databases were used to this end. The Regional Health Information System of FVG was used as the source of information for this retrospective cohort study. The system covers the entire regional population and includes various electronic health administrative databases that can be linked with one another on an individual basis through a unique encrypted identifier. In particular, the following databases were matched: the database of the health care beneficiaries (including demographic information and the residential history of all of the subjects living in FVG), the hospital discharge database, the database of exemptions from medical charges, the database of the laboratories. The population under study was selected based on the following inclusion criteria: patients were residents in the province of Udine and they had to carry the exemption code for AAV, including GPA, or EGPA, or MPA. This population was observed from 2010 to 2018. Results: 57 patients (201 patient-years) with AAV were identified. They were ANCA-positive in 44/57 (77%). GPA, EGPA and MPA was diagnosed in 18 (31, 6%), 15 (26, 3%), 11 (19, 3%) patients, respectively. The mean age at diagnosis was 54, 5 (17, 5) years. The disease itself was the main cause of hospitalization in almost half of the hospital discharges (60/126, 47, 6%). Four patients died during the observation period due to vasculitis itself (1), pneumonia (2), or haematological malignancy (1). Time to the first event (death or hospitalization) was significantly higher in ANCA-negative AAV patients than in ANCA-positive AAV patients (p=0, 03, Log-Rank test), ANCA-positive AAV patients having a three-times higher risk (HR 3, 38 95%CI 1, 13-10, 08, p=0, 03). Total estimated cost was € 1, 215, 078, corresponding to € 6, 168 patient-year. Costs for ANCA-positive AAV patients were much higher than those for ANCA-negative AAV patients (€ 1, 115, 253 vs € 99, 825, and € 7058 per person-year vs € 2, 559 per person-year, respectively). GPA and MPA showed the highest costs if compared to EGPA [GPA: € 239, 168 (€ 5199 per person-year) vs MPA: € 281, 502 (€ 4771 per person-year) vs EGPA: € 214, 287 (2329 per person-year), respectively]. Costs for hospitalization were the highest [€ 734, 957 (€ 3731 per person-year) vs other costs € 480, 121 (€ 2437 per person-year)]. Conclusion: costs for AAV are very high, confirming the high health care burden of this illness. Management of ANCA-positive patients rather than ANCA-negative patients was burdened by the highest costs. GPA and MPA showed the highest direct costs for hospitalization, which very frequently occurred due to the vasculitis itself. Disclosure of Interests: Luca Quartuccio Consultant of: Abbvie, Bristol, Speakers bureau: Abbvie, Pfizer, Elena Treppo: None declared, Salvatore De Vita Consultant of: Roche, GSK, Speakers bureau: Roche, GSK, Novartis, Francesca Valent: None declared